2022
DOI: 10.21037/tp-22-518
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of post-polypectomy bleeding and recurrence in children with colorectal polyps after endoscopic mucosal resection: a retrospective cohort study

Abstract: Background: The incidence rate of colorectal polyps in children has gradually increased in recent years.It is still unclear whether endoscopic mucosal resection (EMR) can be performed in children with colorectal polyps as well as their incidences of post-polypectomy bleeding and recurrence. This retrospective study was performed to explore the feasible of EMR in children with colorectal polyps and analyze the risk factors of post-polypectomy bleeding and recurrence.Methods: Patients aged younger than 18 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…[31] It has also been suggested that pedunculated polyps usually have long, large-bore trophoblastic vessels within the peduncle, and that intraoperative exposure of blood vessels increases the risk of rebleeding and delayed bleeding. [32] In addition, adenomatous polyps (OR = 3.152, 95% CI = 1.018–9.757) are independent risk factors ( P < .05) for postoperative bleeding in patients with colorectal polyps, indicating that adenomatous polyps have an increased risk up to 3.152 times of bleeding after surgery compared with non-adenomatous polyps. This may be due to the fact that adenomatous polyps have a richer blood supply than other types of polyps, [33] which makes them more prone to postoperative bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[31] It has also been suggested that pedunculated polyps usually have long, large-bore trophoblastic vessels within the peduncle, and that intraoperative exposure of blood vessels increases the risk of rebleeding and delayed bleeding. [32] In addition, adenomatous polyps (OR = 3.152, 95% CI = 1.018–9.757) are independent risk factors ( P < .05) for postoperative bleeding in patients with colorectal polyps, indicating that adenomatous polyps have an increased risk up to 3.152 times of bleeding after surgery compared with non-adenomatous polyps. This may be due to the fact that adenomatous polyps have a richer blood supply than other types of polyps, [33] which makes them more prone to postoperative bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…This increased risk may be attributed to the abundant blood supply at the base of pedunculated polyps and their tendency for premature shedding, particularly following certain Endoscopic Variceal Ligation (EVL) procedures. [ 31 ] It has also been suggested that pedunculated polyps usually have long, large-bore trophoblastic vessels within the peduncle, and that intraoperative exposure of blood vessels increases the risk of rebleeding and delayed bleeding. [ 32 ] In addition, adenomatous polyps (OR = 3.152, 95% CI = 1.018–9.757) are independent risk factors ( P < .05) for postoperative bleeding in patients with colorectal polyps, indicating that adenomatous polyps have an increased risk up to 3.152 times of bleeding after surgery compared with non-adenomatous polyps.…”
Section: Discussionmentioning
confidence: 99%
“…Early postpolypectomy bleeding was noted in 5% of patients in one study and was more common in younger patients harboring larger polyps, more often with inflammatory polyp histology. Similarly, postpolypectomy recurrence was more often noted in younger patients with multiple and larger polyps [30].…”
Section: Introductionmentioning
confidence: 99%